2018
DOI: 10.1590/s1413-41522018166513
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da água de rios em cidades do Estado da Bahia

Abstract: RESUMO O monitoramento e a avaliação da qualidade das águas superficiais são de fundamental importância para a gestão sustentável dos recursos hídricos. Nesse contexto, o presente trabalho teve o objetivo de avaliar a qualidade da água de rios localizados em diferentes municípios. Para tanto, foram selecionadas dez cidades do Estado da Bahia, das quais sete contavam com Sistema Público de Esgotamento Sanitário (SES) e três eram desprovidas de tais serviços. Utilizou-se o registro trimestral realizado pelo Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
3
0
6
Order By: Relevance
“…However, for Point 2, only BOD5,20 and Turbidity exceeded the permitted values determined by the current government legislation and regulations (5 mg/L and 40 NTU, respectively) (Table 1), unlike Andrade and Felchak (2009) and Haberland et al (2012), who verified values higher than allowed by legislation in all points sampled in the same river studied here. This result confirms field-work observations, that indicated the possibility of contribution of domestic effluents upstream of collection sites and corroborates the results of Pessoa et al (2018), which found higher BOD5,20 values at points with higher indexes of human occupation.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, for Point 2, only BOD5,20 and Turbidity exceeded the permitted values determined by the current government legislation and regulations (5 mg/L and 40 NTU, respectively) (Table 1), unlike Andrade and Felchak (2009) and Haberland et al (2012), who verified values higher than allowed by legislation in all points sampled in the same river studied here. This result confirms field-work observations, that indicated the possibility of contribution of domestic effluents upstream of collection sites and corroborates the results of Pessoa et al (2018), which found higher BOD5,20 values at points with higher indexes of human occupation.…”
Section: Resultssupporting
confidence: 91%
“…Considering the large occupation area around Point 2 (88% of urban area), it is possible to relate the occurrence of these pathogenic organisms with discharge of sanitary effluents, corroborating the studies of Haberland et al (2012), who verified high values of E. coli in points with the highest human occupation in the Antas River. In spite of this, it is important to emphasize that even though this difference exists, the values of TC and FC in the three points presented values higher than those allowed by Brazilian legislation (Table 1); therefore, areas with a higher percentage of agricultural area do not represent certainty of values according legislation, as also found by Pessoa et al (2018).…”
Section: Resultsmentioning
confidence: 75%
“…Entretanto, devido ao baixo grau de ajuste, é incorreto afirmar que as concentrações simuladas representam a realidade das concentrações de fósforo total encontradas no rio Piracicaba. Blaas et al (2016) No Brasil, diversos outros estudos sobre a qualidade das águas vêm constatando o aumento da poluição e apontando o lançamento de efluentes domésticos sem o adequado tratamento como a principal fonte poluidora (AVILA et al, 2016;CALAZANS et al, 2018aCALAZANS et al, , 2018bCOSTA et al, 2017;FRAGA et al, 2019;OLIVEIRA et al, 2018OLIVEIRA et al, , 2017PESSOA et al, 2018;SOUZA et al, 2014;VARGAS et al, 2018). Conforme ANA (2017), tal fato é reflexo da crítica situação de atendimento da população brasileira em relação ao esgotamento sanitário, onde o déficit de coleta e tratamento de efluentes nas cidades brasileiras tem resultado em uma parcela significativa de carga poluidora que chega aos corpos d'água, causando implicações negativas aos usos múltiplos dos recursos hídricos.…”
Section: Resultsunclassified
“…A pressão antropogênica exercida sobre os ecossistemas aquáticos pode resultar no decréscimo da qualidade de suas águas. Parte dos ambientes aquáticos em meio urbano por todo o planeta encontra-se degradado (RIGOTTI; POMPÊO, 2011;SILVA et al, 2016;KAY et al, 2017;PESSOA;ORRICO;LORDÊLO, 2018;CARSTENS;AMER, 2019;BEGA et al, 2020). As práticas desenvolvidas pela população, o planejamento do uso e da ocupação do solo, a frequência na coleta de resíduos sólidos, a disponibilidade de rede de esgotamento sanitário, a eficiência do sistema de tratamento de águas residuárias e a manutenção de obras de drenagem são fatores condicionantes na conservação dos cursos de água em área urbana.…”
Section: Introductionunclassified